Paediatric HIV projection for the next 5 years—informing service planning and commissioning. (29th September 2015) - Doerholt, K; Boyd, K; Menson, E; Riordan, A; Tudor-Williams, G; Masters, J; Peckham, C; Tookey, P; Sharland, M; Gibb, D
Abstract : Aims: To predict the future number and distribution of HIV-infected children in the UK and Ireland to inform service provision and commissioning practice. Methods: Data to December 2008 from the National Study of HIV in Pregnancy and Childhood and the Collaborative HIV Paediatric Study were used to project the number of HIV-infected children under care in the UK and Ireland over the next 5 years. Assumptions are based on current trends of new HIV diagnoses and exit of infected children to adult care. Sensitivity to these assumptions is considered. Results: In January 2008, 1209 children were under paediatric care. Assuming that current entry, loss to follow-up and death rates remain constant, with transition to adult care remaining at age 17 years, overall predictions show relatively stable numbers in paediatric care over the next 5 years, with a 6% decrease to 1139 children, and median (IQR) age rising from 10.7 (7.4–13.7) years to 11.5 (7.5–14.5) years. Projections for London show a greater decrease of 17%, from 657 to 543 children, compared to an increase of 8%, from 552 to 596 children, outside London. A rise in entry rate of 10% per year and in the age of transition to 18 years would result in an estimated 22% increase in overall numbers to 1481 (697, 6% increase in London). Alternatively, a fall in entry rate of 10% per year and in the age of transition to 16 years would reduce the estimate by 20% to 970 (481, 27% decrease in London). Conclusion: Our projections estimate relatively small changes in the number of HIV-infected children requiring paediatric care over the next 5 years with a continuing redistribution from London to the rest of the UK and Ireland, mainly due to the increasing proportion of newly presenting children being diagnosed outside London. There are currently fewer adolescent clinics outside London, leading to later transition to adult care. These results support the need for continued paediatric HIV service provision to ensure services meet the changing needs of the cohort especially the increasing number of adolescents.